DESIGN AND DEVELOPMENT OF COVID-19 AGENT-BASED MODELLING BASED ON SOCIAL DISTANCE - Gan; Amerudin (Journal of Islamic, Social, Economics and Development, 2022)
COVID-19 is a fatal global pandemic that have been spread throughout the world rapidly. Based on the global statistics, the confirmed cases have been reached 176 million cases at the mid of June 2021. The statistics show how human susceptible to the COVID-19 and how easy the COVID-19 to be spread. Typically, the COVID-19 is transmitted when a healthy person is closed contact with the infected person via the respiratory droplet or saliva. Therefore, social distance has been defined as the main factor that trigger the spread of COVID-19. With the reopening of the primary and secondary schools in Malaysia from March 2021, the formation of new clusters become more seriously. As until 21st April 2021, there are total of 83 COVID-19 clusters is reported that related to the education sector since from early January 2021. The students may come back to the campus for conducting academic activities. Therefore, this study is proposed to analyze the COVID-19 infection inside the campus using Agent-Based Modelling (ABM). The designed ABM has three different settings, which are lecture room, laboratory and office. FABU students and staffs are the agents for the simulation inside the FABU buildings. The factors of COVID-19 infection by the agents are not only considered the social distance between the people, but also ventilation condition of building and exposure time of contact. The designed ABM consists of the parameters such as number of people and social distance to allow the users to analyze the effect towards the COVID-19 infection. Through this model, the administrators could use to plan the classrooms and laboratories to the students for returning back to the campus. This paper suggests to extend the research by developing the designed ABM using AnyLogic software.